Theater with and for the community: An intervention project in the field of adult education - Dos Santos Cunha, Maria José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This article puts forth a project implemented in a rural community, with the aim of, through a theater workshop, getting this community involved, collaborating, valuing and encouraging the participation of its elements so that they may be the builders of their own change. For this purpose, the action-research methodology was used, and the results show that the majority of workshop participants were unanimous in considering that the learning attained through it enabled them to experience a process of change by discovering themselves individually and collectively and, simultaneously, by becoming more creative, interventionist, responsible and preservers of cultural values.